Imidazolium hydrogen carbonate ionic liquids: Versatile organocatalysts for chemical conversion of CO2 into valuable chemicals. Issue 39 (July 2020) - Long, Guangcai; Wu, Dongsheng; Pan, Hongyan; Zhao, Tianxiang; Hu, Xingbang
Highlights: Imidazolium hydrogen carbonate ionic liquids as an organic pre-catalysts for N -heterocyclic carbenes. Imidazolium hydrogen carbonate ionic liquids balance to Cn Cm Im-CO2 serving as the active species for conversion of CO2 . Good to excellent yields of cyclic carbonates and methylamines are obtained for varied substrates. Air and water-stable C1 C6 ImHCO3 was recyclable in up to five consecutive cycles. Abstract: N -heterocyclic carbenes (NHCs) are found to be efficient halogen-free organocatalysts for chemical conversion of CO2, however, their inherent nature is sensitive to water and air, which leads to limitations in practical applications. In this work, we demonstrate the halogen- and metal-free methods for chemical fixation of CO2 into valuable chemicals of cyclic carbonates and methylamines using air and water-stable organocatalysts of imidazolium hydrogen carbonate ionic liquids (Cn Cm ImHCO3 ). Good to excellent yields of cyclic carbonates and methylamines are obtained for varied substrates under mild conditions. Mechanism insight shows that the Cn Cm ImHCO3, as an organic pre-catalysts for N -heterocyclic carbene, can balance to carbene CO2 adduct (Cn Cm Im-CO2 ) serving as the active species for conversion of CO2 . As a result, the halogen- and metal-free organocatalysts of Cn Cm ImHCO3 again emphasize that are possible to replace traditional carbenes and offer an environment-friendly methodology for chemical fixation of CO2 .